2017
DOI: 10.1002/dvg.23020
|View full text |Cite
|
Sign up to set email alerts
|

Oncopeltus fasciatus as an evo‐devo research organism

Abstract: The large milkweed bug Oncopeltus fasciatus was one of the main study insects for a range of biological questions throughout much of the 20 century. Its importance waned with the introduction of Drosophila melanogaster as a genetic model organism. The evo-devo revolution of the turn of the century re-introduced Oncopeltus into the scientific community, and it has proved increasingly useful, mostly within a comparative context for evolution driven research. The last few years have seen a number of significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…Furthermore, Oncopeltus has been an established laboratory model organism for over 60 years, with a rich experimental tradition in a wide range of studies from physiology and development to evolutionary ecology [21-23]. It is among the few experimentally tractable hemimetabolous insect species, and it is amenable to a range of molecular techniques ( e.g ., [24-26]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Oncopeltus has been an established laboratory model organism for over 60 years, with a rich experimental tradition in a wide range of studies from physiology and development to evolutionary ecology [21-23]. It is among the few experimentally tractable hemimetabolous insect species, and it is amenable to a range of molecular techniques ( e.g ., [24-26]).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it was one of the first insect species to be functionally investigated by RNA interference (RNAi, [27]). RNAi in Oncopeltus is highly effective across different life history stages, which has led to a resurgence of experimental work over the past fifteen years, with a particular focus on the evolution of developmentally important regulatory genes (reviewed in [23]).…”
Section: Introductionmentioning
confidence: 99%
“…Our model organism of choice is the milkweed bug Oncopeltus fasciatus (6). Oncopeltus is a member of Paraneoptera, which is the sister group to Holometabola.…”
mentioning
confidence: 99%
“…As such, it is ideally situated as an outgroup to the hyper-diverse and widely studied holometabolous insects, and can serve to polarize changes in the segmentation program in a comparison between the two most widely studied insects: Drosophila and the flour beetle Tribolium castaneum, as well as other holometabolans. Previous work on Oncopeltus has also shown that it tends to be fairly conservative, and represents many ancestral characteristics in its developmental program (6).…”
mentioning
confidence: 99%
“…Unfortunately, these insect orders are all part of the holometabola group of hexapoda, which appeared relatively recently within the insect phylogeny ([9] and references therein). Some efforts have been made in order to fill this gap of studies in hemimetabola animal systems, such as Oncopeltus fasciatus [10], Blattella germanica [11] and water striders [12, 13].…”
Section: Introductionmentioning
confidence: 99%